2019
DOI: 10.1093/mnrasl/slz054
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a possible superflare on Proxima Centauri

Abstract: We report the observation on UT 2017.07.01 of an unusually powerful flare detected in near-infrared continuum photometry of Proxima Centauri. During a campaign monitoring the star for possible exoplanet transits, we identified an increase in Sloan i' flux leading to an observed peak at BJD 2457935.996 that was at least 10% over preflare flux in this band. It was followed by a 2-component rapid decline in the first 100 seconds that became a slower exponential decay with time constant of 1350 seconds. A smaller … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…The maximum of the flare occurs at a similar time for all spectral lines, though we are aware that the real peak of the flare is unresolved in time. Kielkopf et al (2019) report a stellar flare in the M dwarf Proxima Centauri with similar duration as the one detected here. As can be seen in their Fig.…”
Section: The Response Of the Stellar Atmosphere To A Flaring Eventsupporting
confidence: 81%
“…The maximum of the flare occurs at a similar time for all spectral lines, though we are aware that the real peak of the flare is unresolved in time. Kielkopf et al (2019) report a stellar flare in the M dwarf Proxima Centauri with similar duration as the one detected here. As can be seen in their Fig.…”
Section: The Response Of the Stellar Atmosphere To A Flaring Eventsupporting
confidence: 81%
“…Another interesting example is Proxima Centauri. Kielkopf et al (2019) observed a superflare on this star in which the energy of the flare was 100 times the star's luminosity, and such large flares may endanger life on a planet in the habitable zone.…”
Section: Introductionmentioning
confidence: 97%
“…This is especially true for exoplanets orbiting M dwarfs, which are much more active than Sun-like stars. Without a magnetic field to shield against magnetic phenomena such as flares and Coronal Mass Ejections (CMEs), planets around such stars may undergo mass loss and atmospheric erosion on relatively short timescales (see, e.g., Kielkopf et al 2019). The initial mass may also determine whether planets will have moons, a factor which has been hypothesized to play a role in the habitability of a planet, as it does for the Earth.…”
Section: Discussionmentioning
confidence: 99%